(untitled) (Journal of Information Technologies in Education (ITE), 2010)
Fundamental mathematical background is an important part of training future engineers and programmers. The paper considers existing approaches to teaching the fundamentals of discrete mathematics specialist IT profile, a comparative analysis of modern textbooks on discrete mathematics for IT professionals was conducted.